Cell‐to‐cell transmission of C9orf72 poly‐(Gly‐Ala) triggers key features of ALS/FTD. (16th March 2020) - Khosravi, Bahram; LaClair, Kathrine D; Riemenschneider, Henrick; Zhou, Qihui; Frottin, Frédéric; Mareljic, Nikola; Czuppa, Mareike; Farny, Daniel; Hartmann, Hannelore; Michaelsen, Meike; Arzberger, Thomas; Hartl, F Ulrich; et al.
Abstract: The C9orf72 repeat expansion causes amyotrophic lateral sclerosis and frontotemporal dementia, but the poor correlation between C9orf72 ‐specific pathology and TDP‐43 pathology linked to neurodegeneration hinders targeted therapeutic development. Here, we addressed the role of the aggregating dipeptide repeat proteins resulting from unconventional translation of the repeat in all reading frames. Poly‐GA promoted cytoplasmic mislocalization and aggregation of TDP‐43 non‐cell‐autonomously, and anti‐GA antibodies ameliorated TDP‐43 mislocalization in both donor and receiver cells. Cell‐to‐cell transmission of poly‐GA inhibited proteasome function in neighboring cells. Importantly, proteasome inhibition led to the accumulation of TDP‐43 ubiquitinated within the nuclear localization signal (NLS) at lysine 95. Mutagenesis of this ubiquitination site completely blocked poly‐GA‐dependent mislocalization of TDP‐43. Boosting proteasome function with rolipram reduced both poly‐GA and TDP‐43 aggregation. Our data from cell lines, primary neurons, transgenic mice, and patient tissue suggest that poly‐GA promotes TDP‐43 aggregation by inhibiting the proteasome cell‐autonomously and non‐cell‐autonomously, which can be prevented by inhibiting poly‐GA transmission with antibodies or boosting proteasome activity with rolipram. Synopsis: Poly‐GA promotes cytoplasmic mislocalization and aggregation of TDP‐43 via non‐cell‐autonomous proteasome inhibition and ubiquitination within the nuclear localization signal. Proteasome activation and poly‐GA antibodies ameliorate TDP‐43 pathology. Poly‐GA promotes TDP‐43 aggregation by proteasome inhibition even upon cell‐to‐cell transmission. Anti‐GA antibodies reduce TDP‐43 mislocalization. Ubiquitination within the NLS inhibits nuclear import of TDP‐43. Proteasome activation with rolipram ameliorates poly‐GA and TDP‐43 pathology. Abstract : Poly‐GA dipeptide‐repeat expansion in C9orf72 inhibits proteasome activity to cause TDP‐43 pathology even in neighboring cells not carrying it, explaining how TDP‐43 aggregation arises in C9orf72 patients.